Bone tissue reaction to some implants at experiment. - Magrupov, B. A.; Shadmanov, T. T.; Tashpulatov, A. A.; Hodjaev, R. R.; Valiev, E. Y. (Морфологія / Morphologia / Morfologìâ, 2012)
Purpose. To analyze bone repair process in Wistar rats’ thigh, with the use of different biomaterials. Methods. Eighty male rats were used, and standard thigh bone cavities were created in each animal. The cavities were filled with: calcium carbonate, marble powder, allofibroblast culture and autogenous blood clot (control). The animals were euthanized 7, 14, 21, 30 and 60 days after surgery. The thigh bone amputated and submitted to a routine process for histological preparation: staining with Haematoxylin and Eosin (HE). Results. It was detected that all test materials promoted the formation of new bone; however the most marked activation of reparative osteogenesis was observed at implantation of marble powder and allofibroblast culture, less marked at calcium carbonate implantation. Conclusions. The marble and allofibroblast culture implants possess good biocompatibility and osteoinductivity and may serve as ideal material for repairing bone defects.